2022
DOI: 10.1093/mnras/stac1038
|View full text |Cite
|
Sign up to set email alerts
|

Merger-induced galaxy transformations in the artemis simulations

Abstract: Using the ARTEMIS set of 45 high-resolution cosmological simulations, we investigate a range of merger-induced dynamical transformations of Milky Way-like galaxies. We first identify populations of accreted stars on highly radial orbits, similar to the ‘Gaia Sausage’ in the Milky Way. We show that ≈1/3 of the ARTEMIS galaxies contain a similar feature, and confirm that they usually comprise stellar debris from the most massive accreted satellite. Selecting 15 galaxies with discs at the present-day, we study th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 125 publications
(189 reference statements)
4
29
0
Order By: Relevance
“…Furthermore, these HAC/VOD analogs persist over several gigayears, which is consistent with the observationally inferred timeline of the GSE merger. Lastly, the dark matter contribution from GSE is ∼20% within r gal < 30 kpc in this simulation, which is consistent with hydrodynamical simulations of GSE-like major mergers in MW-like galaxies (Fattahi et al 2019;Dillamore et al 2021).…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, these HAC/VOD analogs persist over several gigayears, which is consistent with the observationally inferred timeline of the GSE merger. Lastly, the dark matter contribution from GSE is ∼20% within r gal < 30 kpc in this simulation, which is consistent with hydrodynamical simulations of GSE-like major mergers in MW-like galaxies (Fattahi et al 2019;Dillamore et al 2021).…”
Section: Introductionsupporting
confidence: 88%
“…For example, Emami et al (2021) report that only 32% of Milky Way-like galaxies in the Illustris TNG50 simulation (Nelson et al 2019;Pillepich et al 2019) show simple DM halos, and the rest of the sample exhibit either twisted (gradually rotating) or stretched (abruptly rotating) halos. Prada et al (2019) find that 20% of Milky Way-like galaxies in the Auriga project (Grand et al 2017;Monachesi et al 2019) have twisted halos, while Dillamore et al (2021) find that most galaxies in the ARTEMIS simulations (Font et al 2020) that show GSE-like features exhibit a global change in orientation of their DM halo. In EAGLE simulations (Crain et al 2015;Schaye et al 2015), Shao et al (2021) find that the DM halo of galaxies are well aligned with the common orbital plane of their satellite galaxies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These modeling attempts agree that the dwarf's SFH was shut down between 8 and 10 Gyr ago. Finally, both the progenitor mass and the accretion time can be gauged by comparing the observed redshift z = 0 properties of the tidal debris cloud with its numerical counterparts in galaxy formation simulations (see Belokurov et al 2018;Bignone et al 2019;Fattahi et al 2019;Elias et al 2020;Dillamore et al 2022). Across different simulation suites, these studies find that the accretion events that lead to creation of a highly radially anisotropic metal-rich stellar halo structure near the Sun typically take place 7-10 Gyr ago and that the progenitor galaxies bring between 10 8 and 10 9 M e of stars.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, pure N-body models (Koppelman et al 2020;Naidu et al 2021) constrained the GSE dwarf to be on a retrograde orbit (with respect to the MW's disk rotation) with low-tointermediate circularity, and with a low-inclination angle between its orbital plane and the MW's disk plane. GSE-like mergers have also been identified/studied in cosmological simulations of MW-like galaxies (e.g., Bignone et al 2019;Fattahi et al 2019;Mackereth et al 2019;Elias et al 2020;Grand et al 2020;Dillamore et al 2022). For example, Fattahi et al (2019) selected MW-like galaxies in Auriga (Grand et al 2017) and found that about one-third of them have a highly anisotropic, metal-rich, [Fe/H] ≈ −1, stellar halo, which becomes isotropic at lower metallicities, i.e., just as is observed in the MW.…”
Section: Introductionmentioning
confidence: 99%